Penggunaan Media Digital Canva Dalam Meningkatkan Kreativitas Siswa Membuat Poster Persuasif - Damayanti, Damayanti; Ramly, Ramly; Wahab, Wahab (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to describe the use of digital media canva in improving student creativity in making persuasive posters in class XI.1 SMA Negeri 5 Makassar. This research is a class action research. The subjects in this study were 36 students from class XI.11 SMA Negeri 5 Makassar. Research data were obtained during the planning, action implementation, observation, and reflection stages through tests, classroom observation, and documentation. The tests carried out included initial tests, cycle I tests, and cycle II tests. The instruments used in data collection included observation sheets of teacher and student activities, as well as the task of making persuasive posters. Data analysis techniques used qualitative and quantitative approaches. The results showed that in the first cycle, the results showed that only 22.2% of students (8 out of 36 students) reached the completion criteria, while 77.8% of students (28 out of 36 students) had not reached the completion. After improvement and repetition in the second cycle, the percentage of students who achieved mastery increased significantly to 80.5% (29 students). This change shows that the learning approach applied in cycle II, such as the use of more interactive methods and intensive guidance in the use of Canva digital media, successfully met the research objectives. Thus, this study succeeded in improving the creativity of students in class XI.11 at SMA Negeri 5 Makassar in creating persuasive posters.